Strengthening Community-Based Entrepreneurship: The Significance of Community Capacity Building and Enabling Ecosystem - Suryani, Adi; Soedarso; Utomo, Christiono; Endarko; Ahmad, Imam Safawi (Indonesian Journal of Development Studies, 2022)
Currently, community-based entrepreneurship is regarded as an alternative solution to recover community’s economic condition from crisis. Even more, it can be potential business venture to open more employment, alleviate poverty, reduce urbanization and increase community’s life quality. Despite its enormous benefits, the development of rural community-based entrepreneurships is still inhibited by some major barriers. Those barriers range from physical, hard, infrastructure to soft, human, capacity aspects. To increase its productivity, respond to more competitive business market and be sustainable, today’s community entrepreneurs need to develop more skills, persist positive business attitude and strong mentality. The study aims to explore roles of capacity building and supportive environment in promoting community-based entrepreneurship. The study adopts qualitative research method. The data are gathered and extracted from a community service program. This program aims to increase community entrepreneurs’ capacity of several small and medium scale enterprises at Lumajang. The study finds that the local entrepreneurs need more knowledges and skills on marketing and online promotion to increase their productivity and become more competitive in digital era. The study also indicates that the growth of local entrepreneurs needs to be supported by innovative and openness, networking and partnership.